Assessment of Cardiac Rate and Rhythm in Fetuses with Arrhythmia via Maternal Abdominal Fetal Electrocardiography - Hari K. Narayan; Emilia F. Vignola; William P. Fifer; Ismee A. Williams (Thieme Medical Publishers, Inc., 2015)
Abstract Objective This study aims to report our experience using the Monica AN24 (Monica Healthcare Ltd., Nottingham, United Kingdom), a maternal transabdominal fetal electrocardiographic monitor, in a case series of fetuses with arrhythmias. Study Design We recorded fetal electrocardiograms (fECGs) on subjects with fetal arrhythmias diagnosed by fetal echocardiogram. Fetal heart rate and rhythm were determined via manual fECG analysis. Results Overall, 20 fECGs were recorded from a pool of 13 subjects. Fetal heart rate acquisition was determined to be high, medium, and poor quality in 10, 3, and 7 tracings, respectively. High-quality tracings were obtained in 9 of 11 subjects with gestational age < 26 or > 34 weeks. P waves were detectable in five tracings. Conclusion In subjects < 26 or > 34 weeks' gestational age, there was reasonable success in fetal heart rate acquisition. Further study is warranted to determine the potential role of this device in the monitoring of subjects with fetal arrhythmias.